2019
DOI: 10.3390/app9245453
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Visible Light Communication in Intelligent Transportation Systems: Impact of Snow and Rain

Abstract: A comprehensive study of outdoor visible light communication (VLC) under snow and rain effects has been conducted in this paper. This paper analyzes the expected rain attenuation of Marshal, Carbonneau, and Japan models at different precipitation levels. Snow attenuation is measured in wet and dry situations at various precipitation levels as well. Therefore, a full comparison is carried out for different attenuation effects on certain outdoor VLC design characteristics such as the maximum signal-to-noise rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Hence, weather phenomena block part of the light affecting, in turn, the SNR and the communication range. The effect of the snow is probably the most disruptive on automotive VLC, as dense snowfall can reduce the VLC communication distance by up to 60-80%, as demonstrated by simulation means [40]; iv. in order to have connectivity between the VLC transmitter and the VLC receiver, the emitted light must reach the photosensitive surface and, thus, the line-of-sight condition is mandatory and affects the mobility and the connectivity of the automotive VLC link.…”
Section: Automotive Vlc Specific Issuesmentioning
confidence: 95%
See 2 more Smart Citations
“…Hence, weather phenomena block part of the light affecting, in turn, the SNR and the communication range. The effect of the snow is probably the most disruptive on automotive VLC, as dense snowfall can reduce the VLC communication distance by up to 60-80%, as demonstrated by simulation means [40]; iv. in order to have connectivity between the VLC transmitter and the VLC receiver, the emitted light must reach the photosensitive surface and, thus, the line-of-sight condition is mandatory and affects the mobility and the connectivity of the automotive VLC link.…”
Section: Automotive Vlc Specific Issuesmentioning
confidence: 95%
“…unlike other wireless communication technologies, in VLC the optical carrier is perceivable to the human eye, and so, the optical transmission power is strictly determined by the lighting device primary purpose and by light regulations, with no possibility to increase it; iii. automotive VLC applications must cope with a multitude of weather phenomena that influence the light passage; thus, heavy dust can block part of the light [35], fog and rain influence the light passage by means of reflection, refraction, absorption, and scattering [36][37][38], whereas sleet and snow also affect the light passage affecting the received optical power [39,40]. Hence, weather phenomena block part of the light affecting, in turn, the SNR and the communication range.…”
Section: Automotive Vlc Specific Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the unpredictability of the vehicular VLC channel is further amplified by the unpredictability of the multitude of meteorological conditions and phenomena that can influence the passage of the optical data carrier. Thus, the water particles from rain or fog can influence the light passage through a combination of reflection, refraction, absorption, and scattering [2,11,15,41,42], whereas the snow or heavy dust block part of the optical channel [2,42,43]. All these phenomena eventually lead to a lower optical power detected by the VLC receiver [2,11,15,[41][42][43], which in turn affect the SNR, the communication distance, and the BER.…”
Section: Meteorological Conditions Associated Issues and Solutionsmentioning
confidence: 99%
“…The experimental results performed at 1 m in laboratory conditions demonstrated that the proposed approach enables a VLC system to have a reliable connection in a fog-impaired optical channel and a relatively high SNR. The authors of [42] performed a simulation analysis concerning the effect of rain and snow on I2V VLC, showing that the attenuation introduced by snow is higher than the one due to rain for the same precipitation rate. The results also showed that the communication distance of an I2V VLC link can be decreased by 20%-80% due to snow and by 8%-30% due to rain.…”
Section: Meteorological Conditions Associated Issues and Solutionsmentioning
confidence: 99%